The role of ERAP1 and HLA-B27 in ankylosing spondylitis pathogenesis - Chen, L (2013)
HLA-B27 and ERAP1 are the two strongest predisposing genetic factors to Ankylosing Spondylitis (AS). As a key aminopeptidase in MHC class I presentation, ERAP1 potentially contributes to AS pathogenesis through altering HLA-B27 peptide presentation. In this thesis, I first studied the effect of AS-associated ERAP1 variation on its enzyme activity in vitro. Trimming of two N-terminally extended HLA-B27 epitopes was decreased by K528R mutation; the effect of R725Q was however substrate-dependent. I also investigated the effects of ERAP1 silencing on the repertoire of peptides bound to HLA-B27 and on peptide presentation to Cytotoxic T lymphocytes (CTLs). In both HeLa.B27 and C1R.B27 cells, the proportion of 9mer peptides, the canonical MHC class I peptide length, was decreased by ERAP1 silencing whereas the percentage of longer peptides (11-13mer) was increased. Surprisingly, following ERAP1 silencing, C-terminally extended versions of 9mer and 10mer peptides were readily identified. In both HeLa.B27 and mouse fibroblasts expressing HLA-B27, ERAP1 silencing/knockout reduced recognition by KK10-specific HLA-B27-restricted CTLs following recombinant vaccinia viral infection or transfection with minigenes expressing KK10 precursors. Interestingly, KK10 CTL recognition following extended KK10 minigene transfection was reduced in the presence of the AS protective variant, K528R-ERAP1 compared to wildtype ERAP1. The effects of ERAP1 inhibition (Leucinethiol), silencing (siRNA & shRNA) and introduction in ERAAP-/- cells on cell surface HLA-B27 expression were also studied. My finding validates the role of ERAP1 and HLA-B27 interaction in AS pathogenesis indicated by GWAS. ERAP1 inhibition could potentially be used for treatment in AS and other ERAP1-associated diseases.